Roles of peripheral clocks: lessons from the fly. Issue 3 (16th December 2021) - Yildirim, Evrim; Curtis, Rachel; Hwangbo, Dae‐Sung
Abstract : To adapt to and anticipate rhythmic changes in the environment such as daily light–dark and temperature cycles, internal timekeeping mechanisms called biological clocks evolved in a diverse set of organisms, from unicellular bacteria to humans. These biological clocks play critical roles in organisms' fitness and survival by temporally aligning physiological and behavioral processes to the external cues. The central clock is located in a small subset of neurons in the brain and drives daily activity rhythms, whereas most peripheral tissues harbor their own clock systems, which generate metabolic and physiological rhythms. Since the discovery of Drosophila melanogaster clock mutants in the early 1970s, the fruit fly has become an extensively studied model organism to investigate the mechanism and functions of circadian clocks. In this review, we primarily focus on D. melanogaster to survey key discoveries and progresses made over the past two decades in our understanding of peripheral clocks. We discuss physiological roles and molecular mechanisms of peripheral clocks in several different peripheral tissues of the fly. Abstract : While the central clock in the brain drives daily activity rhythms, most peripheral tissues harbor their own clock systems to generate metabolic and physiological rhythms. In this review, we discuss key discoveries and progress made over the past two decades in our understanding of the roles and timekeeping mechanisms of peripheral clocks in the fly.